Evaluation of aluminum tolerance diversity in Avena sativa L. from the VIR collection - I. G. Loskutov; E. V. Blinova; L. Yu. Novikova (Труды по прикладной ботанике, генетике и селекции)
Background. Oat is an important food and feed cereal crop in Russia. The area under oats is 10 million ha worldwide, and 3 million ha in Russia. Acid soils with excessive content of exchangeable aluminum occupy almost every third hectare in the ex-USSR territory. Oats are relatively resistant to unfavorable soil factors. Among cereal crops, oat is second only to rye and triticale in terms of resistance to exchangeable Al forms. Despite the crop’s high environmental plasticity, an important condition for obtaining sustainable oat yields is the development of new cultivars with resistance to adverse environmental factors, including metal toxicity and high soil acidity.The objective of this work was to search for oat cultivars resistant to soil stressors (excess of Н+ and Al3+) for use in breeding for edaphic resistance.Materials and methods. The research material included 687 oat accessions from the VIR global plant genetic resources collection. The accessions underwent laboratory evaluation of their aluminum tolerance at the initial growth and development stages using the method of measuring radicle growth after the exposure to aluminum stress. Reproducibility of the used modification of the method was mathematically proved.Results and discussion. Significant variation in the resistance to the studied stressor was observed among the accessions. The regions acting as sources of valuable aluminum resistance genes were identified for the crop. The accessions selected for their high resistance to exchangeable aluminum can be used in breeding programs to develop high-yielding oat cultivars with edaphic resistance.